Optimalisasi Penggunaan Bahasa Indonesia dalam Strategi Pemasaran Produk Busana di Media Sosial - Tarigan, Citra Evepania Br; Hetty Novita Sagala; Kesia Sitorus; Bernike Herawati Sijabat; Mayeni Juniati Sormin; Hendra Kurnia Pulungan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The optimization of Indonesian language use in the digital marketing strategy for fashion products on social media is crucial for strengthening the local brand image and increasing consumer engagement. This article analyzes the vital role of the national language in building communication that is persuasive and culturally appropriate. Employing a literature review and content analysis method on the promotional content of local fashion brands such as Erigo and Queenova, this study aims to: 1) analyze the urgency of the Indonesian language in digital marketing, 2) describe the variations in language usage forms in fashion promotion, and 3) present practical strategies for its optimization. The findings indicate that the proper and creative utilization of the Indonesian language provides a competitive advantage, particularly in creating an emotional connection (relatedness) with the audience. Practical strategies for effective language use in the context of digital marketing are also presented.